Intra-EU capital movements: Ten years of Poland's experiences as an EU member in the global context - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2015)
The aim of this paper is to analyse and evaluate the consequences of the establishment of free movement of capital between Poland and the other EU Member States, from the perspective of ten years of Poland's EU membership. Special attention is paid to the role of intra-EU foreign direct investment (FDI) flows into the Polish economy. The widening of the European Union (EU) in 2004 spurred massive and serious legal and economic adjustment processes in the new EU Member States. The free movement of capital is one part of the socalled "four freedoms" within the single European market, and needed to be established in the relations between the EU-15 and new EU Member States. The new EU Member States were granted a relatively short period of time to make those adjustments. However, the establishment of the free movement of capital between Poland and the rest of the EU did not cause disturbances in its economy. In fact it stabilized some spheres of its economic and social life. The intra-EU FDI inflows may be seen as having facilitated the restructuring processes in the Polish economy. The role of foreign investors in employment and foreign trade is decisive for the stabilization of Poland's economic situation. The involvement of foreign investors in innovation processes, although growing, has not radically changed Poland's position in this field. According to the EU innovativeness rankings, Poland belongs to the rank of modest innovators.
Keywords: 330; capital movements; intra EU-foreign direct investment; integration processes; European Union; Poland